Laboratory and exterior decay of wood–plastic composite boards: voids analysis and computed tomography. Issue 5 (20th October 2017) - Sun, Grace; Ibach, Rebecca E.; Faillace, Meghan; Gnatowski, Marek; Glaeser, Jessie A.; Haight, John
ABSTRACT: After exposure in the field and laboratory soil block culture testing, the void content of wood–plastic composite (WPC) decking boards was compared to unexposed samples. A void volume analysis was conducted based on calculations of sample density and from micro-computed tomography (microCT) data. It was found that reference WPC contains voids of different sizes from the micrometer range up to several cubic millimeters. Large voids were unevenly distributed within the composite sample. Void size and volume increased after conditioning the WPC in water at 70°C. Depending on the effect of exposure conditions, fungal decay during laboratory soil block testing increased the size and volume of voids. For laboratory samples, the calculated void volume was much higher compared to microCT-detected voids because of the limited resolution of the instrument on relatively large samples with many nano- and microvoids present in the material. In both laboratory and field samples, the creation of the voids resulted in a significant decrease in composite density. Decay damage observed as an increase in the size and volume of voids was particularly severe for boards exposed in the field. The calculated void volume in such samples was in reasonable agreement with voids detected by microCT.